Safety and Cost-Savings of Same-Day Discharge Trans-Radial Percutaneous Coronary Intervention in Trinidad and Tobago - Ramsingh, Richard (Cureus, 2020)
Introduction: Same-day discharge percutaneous coronary interventions (SDD-PCI) may be quite impactful on healthcare burden for small island developing states (SIDS) such as Trinidad and Tobago. Methods: From June 2012 to November 2014, 11 patients underwent SDD trans-radial PCI and followed up at one-month and three months. Data was retrospectively reviewed from a prospectively entered unit-maintained cardiology database. Baseline patient characteristics, in-hospital expenditure, and complications were assessed. Descriptive statistical analysis was performed in Microsoft Excel. Results: The mean age at SDD-PCI was 50.90±9.96 and nine were male. Nine patients were of East Indian Caribbean ethnicity. Six were diabetic and five were hypertensive. Procedural success was 100% with no major early complication or three-months complications; patient satisfaction was achieved with a potential in-hospital savings up to $1480 USD per patient. Conclusion: This SDD approach for elective trans-radial PCI may be safe and cost-effective in properly selected patients and merits a review of relevant policy issues in Trinidad and Tobago.